Training on Making Hygienic Laundry Soap Based on Home Industry for Housewives in Jambur Village, Padang Matinggi - Rizkiyah Purnama; Muthiatul Khairiyah Ritonga; Raufan Syiddik Harahap; Zulhimma Zulhimma (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
Strengthening the family economy through the development of productive household-based businesses is an important strategy in supporting sustainable rural community development. This approach is considered effective because it utilizes the potential of local resources and involves the active role of family members, especially housewives, in economic activities. One form of business that is relatively easy to implement is the production of hygienic laundry soap, considering the simple manufacturing process, affordable production costs, and has a relatively stable level of market need and demand. These conditions make this business an opportunity to be developed as a productive household economic activity. This study aims to analyze the implementation of home-based hygienic laundry soap production training and examine its impact on improving the skills and economic independence of housewives in Jambur Village, Padang Matinggi . The focus of the study is directed at the training process, the level of understanding of participants, and changes in attitudes and economic capabilities after participating in the activity. The approach used in this study is a descriptive qualitative method, which allows researchers to obtain an in-depth picture of the program implementation and participants' experiences. Data collection techniques are carried out through direct observation, interviews with participants and related parties, and documentation of activities to support research data. The research results show that the training on making hygienic laundry soap had a positive impact on improving the knowledge and skills of housewives in producing safe, hygienic, and marketable soap. Participants not only understood the production stages but also learned how to make soap independently. Furthermore, the training fostered entrepreneurial motivation and awareness of home-based business opportunities, thereby opening up opportunities to increase family income. Therefore, this training program significantly contributes to women's empowerment and strengthening family economies at the village level through the development of productive, home-based businesses.